STRENGTHENING ENVIRONMENTAL EDU-LITERACY THROUGH THE IMPLEMENTATION OF THE ADIWIYATA PROGRAM - Deby Luriawati Naryatmojo; Wahid Akhsin Budi Nur Shidiq; Inaya Sari Melati; Dhita Prasisca Mutiatari (CV. TOTUS TUUS, 2026)
Low participation of school members in waste management and the limited integration of environmental education into the school curriculum are key challenges in implementing the Environmental Care and Culture Movement in Schools (PBLHS) at SMP Al-Fattah Tambakrejo, Semarang City. This research employed a community-based participatory action design involving teachers, students, and Adiwiyata cadres as active partners. The program was implemented over an eight-month period through four main stages: (1) needs assessment and initial coordination, (2) capacity building via training and workshops on environmental literacy, leadership, and waste management, (3) provision of eco-friendly facilities including reusable eating–drinking utensils and a maggot cultivation unit for organic waste processing, and (4) mentoring and evaluation of behavioral change. Data were collected through pre-test and post-test questionnaires, observation of waste generation, and documentation of lesson plan (RPP) integration. The findings show an increase in the number of teachers incorporating environmental topics into RPPs, a 50% rise in student participation in waste reduction activities, and a measurable decrease in single-use plastic and food waste generation. The study demonstrates that combining curriculum integration, student leadership empowerment, and simple waste processing technology can significantly strengthen environmental edu-literacy and foster a sustainable school culture.